Digital Transformation of Minahasa Thanksgiving Ceremony: Analysis of Symbolic Meaning Shift in the Social Media Era - Veronike E.T Salem; Romi Mesra (PT. NALURI EDUKASI PRESS, 2024)
This study aims to analyze the digital transformation of Minahasan thanksgiving ceremonies and the shift in their symbolic meanings in the era of social media. Using a qualitative approach with a systematic literature review method, this study examines various academic and secondary sources to understand the impact of digitalization on the practice and meaning of this traditional ritual. The results show a significant shift in the way thanksgiving ceremonies are carried out, documented, and interpreted. Social media has become a primary platform for sharing ritual experiences, shifting the focus from spiritual aspects to visual and performative aspects. There is also a reinterpretation of traditional symbols in a digital context, as well as changes in the dynamics of participation and social interaction during the ceremony. Although digital transformation brings challenges in maintaining the authenticity of the ritual, it also opens up opportunities for the preservation and promotion of Minahasan culture more broadly. This study highlights the importance of a balanced approach that maintains the cultural essence of thanksgiving ceremonies while utilizing the potential of digital technology to strengthen cultural identity.